Participação, cultura e socialização política juvenil em Cascavel/PR: um estudo a partir dos movimentos em rede - Minucelli, Conrado Pereda (2015)
The research investigates the relationship between the democratic experiment of the protests of June 2013 and the short-term changes in the political socialization of public high school students in Cascavel, Paraná State. Based on the concepts of Political Culture, Participation and Political Socialization, the study took as analytical parameter the movements networking, intending in a comparative perspective, identify the continuities and discontinuities of the political attitudes of young people surveyed after the movements. The movements and the network society was portray as a new development tool and an encouraging to participation in political and community spheres, it was notice that the upward trend in social capital stock and the gradual consolidation of social networks as one of the main communication channel of young people with the local and national political system. The survey applied in 2014 allows the crossing with previous research data and it was base on researches from well-recognized institutions for the Brazilian and international scientific community. The 503 questionnaires answers provided data to outline the key aspects of political socialization and participation among the target public by checking the socio-economic profile of the subjects and measuring their political and interpersonal trust levels, perceptions of citizenship and satisfaction with democracy as well as opinions and feelings about the movements in the network and their contributions. Through these variables, it was observe that the low levels of trust and participation assume continuity, however with significant increases in conducting to participatory activities, information about politics and the use of new information technologies for the organization and mobilization of the youth policies agendas. It was evident that the participation in the networked protests assumed significant activity in the growing trend in the share of respondents in the political affairs, having gradually assumed the virtual communities a socializing role in transforming the studied youth political culture.